2021
DOI: 10.3389/fonc.2021.664403
|View full text |Cite
|
Sign up to set email alerts
|

Carnosol Is a Novel Inhibitor of p300 Acetyltransferase in Breast Cancer

Abstract: Carnosol, a natural polyphenol abundant in edible plants such as sage, rosemary, and oregano, has shown promising anticancer activity against various types of cancers. Nonetheless, very little is known about its molecular mechanism of action or its downstream target(s). We have previously shown that carnosol inhibits cellular proliferation, migration, invasion, and metastasis as well as triggers autophagy and apoptosis in the highly invasive MDA-MB-231 breast cancer cells. Here, we report that carnosol induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…An increase in the overall protein polyubiquitination was as well as mTOR degradation was detectable as early as 3 hours post-carnosol treatment ( Figure 7C ). Because we had previously shown that carnosol also induced a proteasome degradation of STAT3 ( 31 )as well as p300 ( 34 )and PCAF ( 34 ) histone acetyltransferases, we decided to determine the time at which this degradation occurs. As shown in Figure 7C , similar to mTOR’s, PCAF degradation was detected as early as 3 hours post-treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the overall protein polyubiquitination was as well as mTOR degradation was detectable as early as 3 hours post-carnosol treatment ( Figure 7C ). Because we had previously shown that carnosol also induced a proteasome degradation of STAT3 ( 31 )as well as p300 ( 34 )and PCAF ( 34 ) histone acetyltransferases, we decided to determine the time at which this degradation occurs. As shown in Figure 7C , similar to mTOR’s, PCAF degradation was detected as early as 3 hours post-treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We also reported that carnosol induces ROS-mediated beclin1-independent autophagy and apoptosis in triple-negative breast cancer ( 30 ). More recently, we showed that carnosol selectively inhibits the p300 histone acetyl transferase in breast cancer cells ( 34 ). Here, we show that carnosol triggers a ROS-dependent ER-stress response through activation of the three ER stress sensor pathways in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…EP300 is one of the most studied HATs, encoded by the E1A binding protein P300 ( EP300 ) gene which mediates histone and non-histone protein acetylation, and it is involved in gene activation [ 46 , 107 ]. Moreover, high expression and activity of EP300 was demonstrated to be associated with various diseases and malignancies, including pulmonary fibrosis [ 46 ], nasopharyngeal carcinoma (NPC) [ 108 ], hepatocellular carcinoma (HCC) [ 109 ], non-small cell lung cancers (NSCLC) [ 110 ], prostate cancer (PCa) [ 111 ], and breast cancer (BC) [ 112 ]. Moreover, EP300 is associated with several neurodegenerative disorders [ 113 ].…”
Section: Epigenetic Modifications In Breast Cancermentioning
confidence: 99%
“…Mice expressing a truncated EP300 protein in the hippocampus, amygdala, cortex, and cerebellum were shown to have memory deficits in contextual fear conditioning and object recognition tasks [ 114 ]. Additionally, knockdown and pharmacological inhibition of EP300 were shown to reduce tumor growth and metastasis in vitro and in a xenograft mouse model of BC in vivo [ 112 , 115 ]. In addition to EP300, GCN5 is another family member of HATs that was found to play a key role in the TGF-β/SMAD signaling pathway in breast cancer cells [ 116 ].…”
Section: Epigenetic Modifications In Breast Cancermentioning
confidence: 99%
“…Carnosol, which takes the region binding acetyl-CoA’s pantetheine arm, is verified to be the candidate anti-BC target. In addition, it is the new natural p300 inhibitor, which can be listed in the current inhibitor panel ( Alsamri et al, 2021 ).…”
Section: Histone Acetylation Targeted Anti-cancer Drugsmentioning
confidence: 99%